Graduação em enfermagem: aprendendo a aprender a reforma psiquiátrica brasileira Nursing graduation: learning how to learn the Brazilian psychiatric reform - Agnes Olschowsky; Sonia Barros (SciELO, 1999)
Este trabalho tem como objetivo identificar as mudanças incorporadas no ensino de graduação em enfermagem psiquiátrica. O estudo identifica a preocupação com a atualização do ensino na área, em que a transformação do docente, a participação e a construção de uma nova concepção sobre o saber e as práticas psiquiátricas, possibilitam novas formas de aprender a aprender a reforma psiquiátrica brasileira. This paper aims at identifying the changes that became part of the theaching of psychiatric nursing. The study points out the concern regardin teaching updating in this area in which the teacher's transformation, participation and the creation of a new concept about psychiatric knowledge and practice make it possible to have new ways to learn how to learn the brazilian psychiatric reform.